PURIFICATION AND PARTIAL CHARACTERIZATION OF SERUM IMMUNOGLOBULIN FROM PERSIAN STURGEON (ACIPENSER PERSICUS) - M. Kalbasi1; A. Mostafaei2; J. Majidi3 (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2003)
In this study, immunoglobulins from serum of Persian sturgeon (Acipenser persicus) were purified and partially characterized. Immunoglobulins were purified from the pooled sera by a combination of salt precipitation, Ion-exchange chromatography and gel filtration methods. DEAE sepharosefast flow and sepharose CL-6B columns were used for Ion exchange-chromatography, and gel filtration, respectively. The purity, molecular weight and molecular distribution of the immunoglobulin preparations was determined by gel electrophoresis (SDS-P AGE) in reducing and non-reducing situations. In gel filtrated immunoglobulins two distinct peaks, high molecular weight (HMW Ig) and low molecular weight (LMW Ig) were obtained. Both HMW Ig and LMW Ig had identical heavy and light chains of 72-75 KDa and 27-29 KDa, respectively, in reducing SDS-P AGE. HMW Ig contained a group of bands, including two major bands in non-reducing SDS-PAGE, In contrast LMW Ig contain more than half of the total immunoglobulin, was 190 KDa. In ion exchange chromatography, immunoglobulins were eluted in three peaks. The first was exclusively monomer and others were mixture of monomer and polymers. This is the first report on persian sturgeon immunoglobulins. Results of this investigation showed that persian sturgeon immunoglobulins was not homogenous in respect of molecular distribution, PI and the type of light chain. The presence of more than one genes for light and\or heavy chains or post transcriptional and\or post modifications may be responsible for these variations.